Variations of Thermospheric Winds Observed by a Fabry–Perot Interferometer at Mohe, China. Issue 2 (28th January 2021) - Li, Wenbo; Chen, Yiding; Liu, Libo; Trondsen, Trond S.; Unick, Craig; Wyatt, Devin; Ning, Baiqi; Li, Guozhu; Huang, Cong; Yang, Sipeng; Le, Huijun
Abstract: A Fabry–Perot interferometer (FPI) system was deployed to observe the thermospheric winds at Mohe (53.5°N, 122.3°E), the northernmost observatory of space environment in the mainland of China, in July 2019. Thermospheric winds variations revealed from the 1 year FPI observations are as follows: (1) For the diurnal variation, southward meridional winds prevail at night and peak after midnight with amplitudes from 70 to 110 m/s; meridional winds are northward (∼40 m/s) at dusk and dawn in winter. For the zonal winds, eastward winds prevail only at dusk in summer, while it can sustain after midnight in winter. The maximum amplitudes of eastward winds are 50–130 m/s. Westward winds are strongest at dawn, with amplitudes of 75–120 m/s. (2) For the seasonal variation, both the meridional and zonal winds are dominated by annual oscillations. The semi‐annual oscillations can be observed at midnight. (3) The eastward (southward) winds become strong (weak) at midnight in January and December. An empirical model of thermospheric winds was established based on Mohe FPI observations and compared with HWM14. The variation trends of thermosphere winds described by HWM14 is basically consistent with the observations at Mohe. Moreover, Mohe FPI observations were compared with those by Kelan (38.7°N, 111.6°E) FPI. Variations of thermospheric winds showed some discrepancies between these two locations. The southward winds were significantly stronger at Mohe than at Kelan after midnight; and the semi‐annual and tri‐annual oscillations in the midnight zonal winds are observed at Mohe but not significant at Kelan. Key Points: The 1‐year thermospheric winds observations from a new Fabry–Perot interferometer deployed at Mohe, China, are presented The diurnal and seasonal variations of thermospheric winds at Mohe are investigated and discussed An empirical model of thermospheric winds at Mohe is established and compared with the HWM14 model